PENINGKATAN KAPASITAS PENYULUH DAN PETANI MELALUI DIGITALISASI MATERI PENYULUHAN DI DESA ULANTA KECAMATAN SUWAWA KABUPATEN BONE BOLANGO - Nur Silfiah Amin; Karlena Arsyad; Delvi Suleman (Universitas Mataram, 2026)
This community service program was conducted by lecturers and students of the Faculty of Agriculture, Gorontalo State University, under the theme “Enhancing the Capacity of Agricultural Extension Workers and Farmers through the Digitalization of Extension Materials in Ulanta Village, Suwawa District, Bone Bolango Regency.” The program was motivated by the low level of digital literacy among extension workers and farmers, as well as the absence of a structured and sustainable system for documenting and distributing agricultural extension materials in digital form. The main objective was to improve the participants’ ability to utilize digital technology as an effective, interactive, and accessible medium for agricultural extension. The activity employed a participatory and learning-by-doing approach, consisting of several stages: needs assessment, technical training on the use of Canva and CapCut applications, practical sessions for producing digital content, and the establishment of a WhatsApp Group as a community-based extension platform. Evaluation was conducted through pre-tests and post-tests to measure the improvement in participants’ knowledge and skills. The results showed a significant increase in participants’ digital competencies, where the farmers’ average post-test score rose from 13.35% to 76.24%, and the extension workers’ score increased from 22.4% to 95.9%. Participants successfully produced two types of digital extension materials (a short video and an infographic) and actively used the WhatsApp Group to share agricultural information. The program also resulted in a transformation of the extension workers’ role—from conventional information providers to digital facilitators—and fostered greater independence among farmers in accessing and producing agricultural information. In conclusion, the program effectively enhanced the digital literacy and technical skills of extension workers and farmers, strengthened information exchange through digital communication platforms, and demonstrated the potential for developing a sustainable model of digital agricultural extension at the village level.